A Descriptive Study to Assess the Knowledge and Practices Regarding Prevention of Urinary Tract Infection (UTI) among Adolescent Girls at Selected Higher Secondary Schools - M. Patel, Ekta; L. Pari, Mamta; P. Rathva, Nayana; H. Chauhan, Josmita; S. Varia, Hima (International Journal of Psychosocial Rehabilitation, 2020)
Background of the study: Urinary tract infection is one of the most usual adolescent girl’s infections. Permanent renal cortical scarring may occur in effect girls, especially with urinary tract infection, leading to long-term complications. A urinary tract infection is a common infection that can upset any part of the urinary system. Among adolescent girls, lower urinary tract infections are very common. At least one episode of urinary tract infection will occur in nearly 5-6% of girls from first grade to graduation from high school. Compared to boys, the recurrence rate is 50% greater in girls. Due to urinary tract infections, every year nearly 6-7 million young women visit physicians. The present study was conducted with the aim to assess knowledge and prevention practices regarding urinary tract infections among adolescent girls.Material and method: In this study cross-sectional descriptive survey research design was used. The simple random sampling technique was used to collect samples. Data collection was done by administering the structured knowledge questionnaire and self-reported practice checklist.Results: Descriptive and inferential statistics were used. The result reveals that most of the samples (71.5%) had poor knowledge, and the majority (87%) had poor practice standards.Conclusion: A significant poor knowledge and practice was found regarding prevention of urinary tract infection among adolescent girls. Health care professionals and facilities have the responsibility to broadcast proper information about urinary tract infections so that women will be made aware of the causes, risk factors, symptoms, and prevention practices of urinary tract infections.